Intracellular African swine fever virus DNA remains unmethylated in infected Vero cells - Weber, Stefanie; Hakobyan, Astghik; Zakaryan, Hovakim; Dörfler, Walter (Epigenomics, 2018)
Aim: Sequence-specific CpG methylation of eukaryotic promoters is an important epigenetic signal for long-term gene silencing. We have now studied the methylation status of African swine fever virus (ASFV) DNA at various times after infection of Vero cells in culture. Methods & results: ASFV DNA was detectable throughout the infection cycle and was found unmethylated in productively infected Vero cells as documented by bisulfite sequencing of 13 viral DNA segments. Conclusion: ASFV DNA does not become de novo methylated in the course of infection in selected segments spread across the entire genome. Thus DNA methylation does not interfere with ASFV genome transcription. Lack of de novo methylation has previously been observed for free intracellular viral DNA in cells permissively infected with human adenoviruses, with human papillomaviruses and others.
EVALuna2:35287